EVALUATION IN MATHEMATICS USING SOFTWARES. METHODOLOGICAL REFLECTIONS - ZASTÎNCEANU, Liubov (Acta et Commentationes, Sciences of Education, 2022)
Computer-assisted evaluation in mathematics has been and remains a rather difficult activity. The experience, gained by mathematics teachers in the Republic of Moldova over the last two years in this regard, highlights aspects specific of the local educational process. The article analyzes data from a survey conducted among mathematics teachers in the country, the experience of the teachers themselves and the author’s experience in using computer-assisted assessment. At the end some conclusions and suggestions are formulated about methodological conclusions and recommendations for the use of software-based evaluations both in distance learning and in direct contact.